2021
DOI: 10.1016/j.buildenv.2021.108367
|View full text |Cite
|
Sign up to set email alerts
|

Weakening personal protective behavior by Chinese university students after COVID-19 vaccination

Abstract: Personal protective behaviors and their dynamic change are known to play a major role in the community spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causal pathogen of the coronavirus disease 2019 (COVID-19) pandemic. In this study, a total of 3229 students in Chinese universities completed an online survey about their knowledge on transmission and personal protective behavior before and after COVID-19 vaccination. Of the respondents, 87.6% had been vaccinated. Most students belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 50 publications
2
24
2
2
Order By: Relevance
“…Compliance with two of the main COVID-19 public health measures, such as wearing a mask and hand washing, slightly increase after the second dose and decrease as a willingness after the booster dose, but what is more concerning is that maintaining physical distancing consistently decreased, from 90.1% to 74.7%, and hand hygiene was more used than physical distancing. In line with the present finding related to the decrease of the compliance, several previous studies using different samples of adults conducted within the past year found that the vaccination leads participants to reduce their compliance with public health measures [ 6 , 8 , 15 ]. Moreover, studies conducted in Italy showed a decrease over time in the behavior or in attitudes towards the adoption of the majority of the protective behaviors towards COVID-19 [ 13 , 16 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Compliance with two of the main COVID-19 public health measures, such as wearing a mask and hand washing, slightly increase after the second dose and decrease as a willingness after the booster dose, but what is more concerning is that maintaining physical distancing consistently decreased, from 90.1% to 74.7%, and hand hygiene was more used than physical distancing. In line with the present finding related to the decrease of the compliance, several previous studies using different samples of adults conducted within the past year found that the vaccination leads participants to reduce their compliance with public health measures [ 6 , 8 , 15 ]. Moreover, studies conducted in Italy showed a decrease over time in the behavior or in attitudes towards the adoption of the majority of the protective behaviors towards COVID-19 [ 13 , 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…Vaccinated people and those who had received the COVID-19 vaccine booster dose, should continue to take all appropriate recommended precautions to protect themselves and others from the disease. To the best of our knowledge, the literature has neglected to investigate the change in plans to use preventive measures among those who had received a COVID-19 booster dose, and only a few studies have analyzed the compliance with the recommended prevention behaviors among vaccinated individuals [ 6 , 7 , 8 , 9 ]. Therefore, in this current epidemiological scenario, the present research offers an important contribution to the existing literature.…”
Section: Introductionmentioning
confidence: 99%
“…China had largely managed to keep imported infections from causing major local outbreaks since the country successfully controlled the domestic spread of SARS-CoV-2 during the first phase of the pandemic. Our previous study showed that university students in China relaxed their personal protective behaviors after vaccination (41). In contrast, this study revealed that the personal protective behaviors of HCWs were sustained after vaccination.…”
Section: Discussioncontrasting
confidence: 69%
“…We observed a lower VE against symptomatic infection for individuals aged up to 59 years old compared to older individuals. We hypothesize this can be related to changes in behavior post-booster-vaccination, lowering the risk perception of getting COVID-19, and adherence to personal preventive measures 18 , 19 , mainly in the younger group 20 , 21 , increasing the risk of infection by the Omicron variant.…”
Section: Discussionmentioning
confidence: 99%